2015
DOI: 10.1097/j.pain.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA decreases interictal CGRP plasma levels in patients with chronic migraine

Abstract: OnabotulinumtoxinA (onabotA) has shown efficacy in chronic migraine (CM). Its mechanism of action, however, remains obscure. We have analysed whether treatment with onabotA is able to induce changes in interictal plasma calcitonin gene-related peptide (CGRP) concentrations, which have been shown to be increased in patients with CM. Calcitonin gene-related peptide levels were determined in samples obtained from the right antecubital vein using ELISA, outside a migraine attack and having taken no symptomatic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 41 publications
4
129
1
5
Order By: Relevance
“…Unfortunately, the present patient group was not so numerous to permit the evaluation of the subgroups treated with amitriptyline and topiramate, who could ideally show a greater improvement of allodynia. Recent studies confirmed that botulinum toxin treatment may reduce Calcitonin Gene Related Peptide in responder patients, another point in favor of its potential action on nociceptive transmission and central sensitization development [28].…”
Section: Obt-a Has Effect On Allodyniamentioning
confidence: 96%
“…Unfortunately, the present patient group was not so numerous to permit the evaluation of the subgroups treated with amitriptyline and topiramate, who could ideally show a greater improvement of allodynia. Recent studies confirmed that botulinum toxin treatment may reduce Calcitonin Gene Related Peptide in responder patients, another point in favor of its potential action on nociceptive transmission and central sensitization development [28].…”
Section: Obt-a Has Effect On Allodyniamentioning
confidence: 96%
“…More recently, OnabotulinumtoxinA injection into rat craniofacial muscles attenuated the vasogenic vasodilation caused by the release of CGRP from muscle nociceptors [70]. In addition, OnabotulinumtoxinA decreases interictal CGRP plasma levels in patients with CM [71] …”
Section: Mechanism Of Actionmentioning
confidence: 97%
“…Vielmehr scheint auch der Einfluss auf eine die periphere und zentrale Sensitivierung, wie sie für die chronische Migräne postuliert werden [7], von Bedeutung zu sein, dies ist mög-licherweise die Erklärung dafür, dass der Wirksamkeitsnachweis zur Behandlung der episodischen Migräne, bei der diese Mechanismen eine geringere oder keine Rolle spielen, bislang nicht gelang. Darüber hinaus weisen ersten Studien daraufhin, dass interiktal bestehende erhöh-te CGRP ("calcitonin gene related peptide") -Spiegel einen Prädiktor für das Ansprechen einer Behandlung mit Botulinumtoxin darstellen könnten [10,11]. Bei erfolgreicher Behandlung kommt es im Verlauf auch zu einem Abfall der interiktalen CGRP-Spiegel, was eine Wirkung von OnabotulinumtoxinA auf die CGRP-Freisetzung nahelegt [11].…”
Section: Migräneunclassified
“…Darüber hinaus weisen ersten Studien daraufhin, dass interiktal bestehende erhöh-te CGRP ("calcitonin gene related peptide") -Spiegel einen Prädiktor für das Ansprechen einer Behandlung mit Botulinumtoxin darstellen könnten [10,11]. Bei erfolgreicher Behandlung kommt es im Verlauf auch zu einem Abfall der interiktalen CGRP-Spiegel, was eine Wirkung von OnabotulinumtoxinA auf die CGRP-Freisetzung nahelegt [11].…”
Section: Migräneunclassified